Effect of Dietary Herbal Antioxidants on Meat Quality of Stressed Broilers - Swathi, B.; Gupta, P.S.P.; Raju , M.V.L.N. (Journal of Meat Science, 2012)
A study was performed with two hundred and sixteen day old vencobb broiler chicks in two batches during summer. In each batch 108 chicks were divided into 9 dietary treatment groups viz.T1- fed on basal diet (BD) alone;T2-BD+viatamin E(200mg/Kg);T3-BD+vitaminE(200mg/Kg) +selenium(0.15mg/kg);T4-BD+Tulsi(0.25%);T5-BD+Tulsi(0.5%);T6-BD+Turmeric(0.2%);T7- BD+Turmeric(0.4%);T8-BD+Tulsi(0.25%)+Turmeric(0.2%);T9-BD+Tulsi(0.5%)+Turmeric (0.4%). Additionally 12 chicks were raised separately in stress free environment that served as the control group. Supplementation of diets with antioxidants ranged from 3.75-4.15(colour), 3.6-4.1(texture), 3.48- 4.0(juiciness),3.5-3.98(Flavor)& 3.6-4.0(overall acceptability) on 5 point hedonic scale. Antioxidant supplementation in different levels and combinations improved the scores over that of heat stressed (HS) with more striking hike with GroupT3.The TBARS (mg of melonoldehyde/Kg) levels was higher in HS group and were reduced in groups T3 followed by group T2.Tulsi at 0.5% and Turmeric at 0.4% were more effective than when supplemented at 0.25 and 0.2%, respectively in reducing MDA concentration. However, combination of herbals at different doses added no additive benefit than their sole inclusions,
Keywords: Broilers; summer stress; antioxidants; herbals and meat quality